Evaluation of Antitumor Activity of Long-Circulating and pH-Sensitive Liposomes Containing Ursolic Acid in Animal Models of Breast Tumor and Gliosarcoma. (December 2016) - Rocha, Talita Guieiro Ribeiro; Lopes, Sávia Caldeira de Araújo; Cassali, Geovani Dantas; Ferreira, Ênio; Veloso, Emerson Soares; Leite, Elaine Amaral; Braga, Fernão Castro; Ferreira, Lucas Antônio Miranda; Balvay, Daniel; Garofalakis, Anikitos; Oliveira, Mônica Cristina; Tavitian, Bertrand
Background . Ursolic acid (UA) is a triterpene found in different plant species, possessing antitumor activity, which may be a result of its antiangiogenic effect. However, UA has low water solubility, which limits its use because the bioavailability is impaired. To overcome this inconvenience, we developed long-circulating and pH-sensitive liposomes containing ursolic acid (SpHL-UA). We investigated the antiangiogenic effect of free UA and SpHL-UA in murine brain cancer and human breast tumor models by means of determination of the relative tumor volume, dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), and histopathological analysis. Methods . The animals were treated with dimethyl sulfoxide in 0.9% (w/v) NaCl, free UA, long-circulating and pH-sensitive liposomes without drug (SpHL), or SpHL-UA. The animals were submitted to each treatment by intraperitoneal injection for 5 days. The dose of free UA or SpHL-UA was equal to 23 mg/kg. Results . Tumor growth inhibition was not observed in human breast tumor–bearing animals. For murine gliosarcoma-bearing animals, a slight tumor growth inhibition was observed in the groups treated with free UA or SpHL-UA (9% and 15%, respectively). No significant change in any of the parameters evaluated by DCE-MRI for both experimental models could be observed. Nevertheless, the evaluation of the mean values of magnetic resonance parameters of human breast tumor–bearing animals showed evidence of a possible antiangiogenic effect induced by SpHL-UA. Histopathological analysis did not present significant change for any treatment. Conclusion . SpHL-UA did not show antiangiogenic activity in a gliosarcoma model and seemed to induce an antiangiogenic effect in the human breast tumor model.